Potentially Inappropriate Durations of Anti-Infective Therapy at Hospital Discharge Despite Inpatient Antimicrobial Stewardship. (4th October 2017) - Fox, Neal; Haines, Lauren; Bull, Rachel; Jenkins, Zachary; Ballentine, John; Burdette, Steven; Pleiman, Craig
Abstract: Background: Excess durations of anti-infective therapy are a common problem that may lead to unintended consequences. Antimicrobial stewardship (AMS) is a growing field that largely focuses on inpatient anti-infective use. For this study, one site was an academic medical center whose AMS uses prospective auditing; the other was a community hospital with pharmacy-driven AMS. Little research has examined durations of anti-infective therapy at hospital discharge. Methods: Patient charts were reviewed and 284 were included in the final analysis. Patients were excluded if discharged on non-oral anti-infectives or only agents for a non-study indication. Patients were included if they were discharged on oral anti-infective therapy for CAP, healthcare-associated pneumonia (HCAP), UTI, cellulitis, and superficial abscess. Evidence-based durations of therapy were utilized to determine the potential inappropriateness of anti-infective therapy. Guidelines from the study period were used. Total duration of therapy was derived from the combination of outpatient therapy plus inpatient therapy beginning with the first day of relevant coverage for the given indication. Descriptive statistics were utilized to compare durations of therapy. Chi-squared tests were utilized to examine differences in expected frequencies. All statistics were performed in SPSS v. 24. Results: The average combined duration of therapy was 11.3 days. 190 patients (66.9%) were found to have a potentially inappropriate duration of oral anti-infective therapy at hospital discharge. Only 2 durations were too short. Figure 1 displays the distribution of excess days of therapy. Figure 2 shows the breakdown of potential inappropriateness of duration by diagnosis. Figure 3 displays the percentage of potentially inappropriate cases by site. There were no significant differences in the primary outcome between the sites. Conclusion: CAP and cellulitis appear to be areas that are often overtreated. Discharge durations of therapy should be a focus of AMS teams. Many patients receive potentially inappropriate durations of therapy at discharge without any discernible benefit. Further research is needed in this area. Disclosures: All authors: No reported disclosures.